Vanadium redox flow batteries: Flow field design and flow rate optimization - Huang, Zebo; Mu, Anle; Wu, Longxing; Wang, Hang (Journal of energy storage, 2022)
•Summarized the crucial issues affecting the development of vanadium redox flow battery.•Comprehensively analyzes the importance and necessity of flow field design and flow rate optimization.•Systematic analyzes the attributes and performance metrics of the battery for evaluating the flow field performance of the vanadium redox flow battery.•Comparative study and analysis of existing flow field design and flow rate optimization methods, looking forward to new ideas in the future flow field design. Vanadium redox flow battery (VRFB) has attracted much attention because it can effectively solve the intermittent problem of renewable energy power generation. However, the low energy density of VRFBs leads to high cost, which will severely restrict the development in the field of energy storage. VRFB flow field design and flow rate optimization is an effective way to improve battery performance without huge improvement costs. This review summarizes the crucial issues of VRFB development, describing the working principle, electrochemical reaction process and system model of VRFB. The process of flow field design and flow rate optimization is analyzed, and the battery attributes and metrics for evaluating VRFB performance are summarized. The focus of the research is the methods of flow field design and flow rate optimization, and the comprehensive comparison of battery performance between different flow field designs. Literature analysis shows that reasonable flow field design can improve the uniformity of electrolyte, improve battery attributes and metrics, and thus improve the overall performance of VRFB and reduce the cost.